An Advanced 3D Mathematical Model for a 6-high Tandem Cold Rolling Process. (2017) - Feng, Xiawei; Montmitonnet, Pierre; Yang, Quan; He, Anrui; Wang, Xiaochen
Abstract: The present paper focuses on the validation of on-going efforts made to develop more advanced 3D mathematical model for cold rolling strip process [8]. Following [2], the model uses the multi-slab strategy to deal with the differential reduction in the transverse direction due to roll deformation, and analytical solutions of roll bending and flattening discretized by the Influence Function Method (IFM). Furthermore, the model has been extended to incorporate elastic deformation of strip and to be fit for 6-high rolling mills with shiftable work roll (WR) or Intermediate Rolls (IR) as well as 4-high mills. Validation is performed by using FEM solutions (Abaqus® implicit) as references: a 2D quasi-static model to check the slab method under rigid work roll condition; a 3D FEM to discuss the assumption of small lateral flow of strip; a comparison of FEM and IFM with regard to 6-high roller stack deformation with intermediate roll shifting. All these steps are essential to gain more insight into the mechanism of cold rolling strip and to guide future development work of the mathematical model.